(untitled) (Journal of Student Affairs in Africa, 2021)
Despite the presence of a historically male-dominated culture in leadership, gendermediated obstacles and challenges, black women in South Africa have the passion to develop professionally and move to higher levels as educational leaders. The current study assessed female students’ perceptions regarding a joint pilot doctoral programme between the University of the Western Cape (UWC) and California State University, Fullerton’s (CSUF) Higher Education programme, and their experiences while in the programme. Five participants described programme expectations, challenges, strengths, weaknesses and programme South Africacompletion. Moreover, the research focused on the participants’ future hopes, aspirations and their observations regarding any changes in their professional and academic growth. Students expressed that coming to CSUF after their experiences at UWC enabled them to learn from faculty members with expertise in student affairs, which has further developed their knowledge concerning student development strategies, philosophy and history. Recommendations for the programme centred on increased cohort meetings, expanded programme resources such as research, student support outside the classroom settings, and the improvement of programme funding in order to provide more financial support to students. The importance of professional development and formalised training programmes, expanding research dynamics, and teaching components with international collaborations are promising practices to address the challenges and obstacles that black women face in preparing to become leaders in South African higher education.